2023
DOI: 10.1097/j.pain.0000000000002975
|View full text |Cite
|
Sign up to set email alerts
|

“I felt uncertain about my whole future”—a qualitative investigation of people's experiences of navigating uncertainty when seeking care for their low back pain

Abstract: Uncertainty pervades low back pain (LBP). This study aimed to explore individuals' experiences of navigating uncertainty when seeking care for their LBP, with a view to better understanding the contexts in which they experience uncertainty and gaining insight into how uncertainty may be better navigated during clinical encounters. We conducted 15 semistructured interviews with people who have experienced LBP. Interviews were audio-recorded, transcribed, and analysed using reflexive thematic analysis. Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Most of the participants expected to be referred to a medical specialist even though they did not know which professional could help them or who was the best care provider for their condition. This finding is similar to a recent qualitative study that reported that people living with LBP are uncertain about the treatment they should receive (Costa et al, 2022). Most of the participants appeared not to understand that being referred to a PT by their FP was the appropriate step to initiate their care, in accordance with evidence-based recommendations (Qaseem et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…Most of the participants expected to be referred to a medical specialist even though they did not know which professional could help them or who was the best care provider for their condition. This finding is similar to a recent qualitative study that reported that people living with LBP are uncertain about the treatment they should receive (Costa et al, 2022). Most of the participants appeared not to understand that being referred to a PT by their FP was the appropriate step to initiate their care, in accordance with evidence-based recommendations (Qaseem et al, 2017).…”
Section: Discussionsupporting
confidence: 84%
“…These findings align with recent literature emphasising the power of narrative methods to express the complexity of feelings, emotions and experiences influenced by sport-specific sociocultural aspects that athletes negotiate daily. [8][9][10] In this paper, the third and final part of the series we present the priorities for future practice as part of an integrated overview and culmination of our overall findings.…”
Section: Introductionmentioning
confidence: 99%